قاعدة سد الذرائع وتطبيقاتها في المعاملات المصرفية المعاصرة - غريسي, كريمة; بوقنة, كنزة (University of Eloued-جامعة الوادي, 2014)
This research aims to show the importance of using the obstruction pretext rule in modern banking treatments. It begins by mentioning the definitions of pretexts by the scholars. Then it shows the difference and the relationship between pretexts and the relevant terms. It indicates the pillars and parts of pretexts by scholars. After that it displays the pretext rule and the doctrines of scholars by arguing in it. The research mentions the concept of modern banking treatments and then treats the characteristics and modern parts banking treatments. It mentions the purposes of Shariah in Islamic bank treatments. Finally the research exhibits examples of applications of pretexts in modern banking treatments that carried out by scholars and Fikh assemblies. Keywords: obstruction pretext - modern banking treatments - funds purposes - foliation banking - loyalty sale
مذكرة ليسانس
Keywords: قاعدة /سد الذرائع/المعاملات المصرفية/المعاصرة; La règle du blocage des prétextes aux transactions bancaires contemporaines